Infeksi odontogen pada sinusitis maxillaris ditinjau dari radiografik panoramik - MARISSA A, - (2010)
Background. Maxillary sinusitis is a relatively common condition in Indonesia, which knowncan caused by odoontogenic and non-odontogenic infection. Panoramic radiograph is a kind ofradiographic examination that can visualize the entire maxilla and mandible including upperteeth and maxillary sinus. Therefore this imaging has the capability as a supportive examinationthat can discover the cause of odontogenic maxillary sinusitis. Purpo$e. The aim of this studywas to acknowledge whether panoramic radiograph can support the diagnose of maxillarysinusitis caused by odontogenic infection. Method. After carried out the panoramic exposures toobserve maxillary sinusitis caused by upper tooth irifection, the panoramic samples wereobserved by 1 student and 2 thesis advisors. Data were analyzed by Binomial Test. Result. FromBinomial Test, significant value was obtained 0,041 (p<O,05). This shows that there was asignificant difference between sample groups. Conclusion. There was a significant difference ofodontogen~c and non-odontogenic maxillary sinusitis viewed by panoramic radiograph ..